Impact of Supplementation on Anemia, Cognition, and Growth in Children: A Scoping Review of Randomized Controlled Trials - Dafa Bintang Nugroho; Anjani Nelka Rachmawatty; Almira Sitasari; Agus Wijanarka; Tri Siswati (Health Dynamics, 2024)
Background: Anemia in children is a global health problem that can affect their cognitive and physical development. Various supplementation interventions have been used to treat anemia, including iron, folic acid, vitamins, and other minerals. Although some studies have shown improvements in anemia status, challenges in adherence to treatment and side effects remain barriers. Objective: This scoping review aims to map the available scientific evidence related to interventions and supplementation in children with anemia. This study identifies the types of interventions used, the target population, and the outcomes reported in the studies. Methods: A literature search was conducted through PubMed and Google Scholar with the keywords "anemia," "intervention," "supplement," and "children." Included studies were publications from 2015 to 2024 involving children who received supplementation interventions to see the impact of supplementation on anemia, cognition, and growth in children. Data from relevant studies were collected and analyzed based on study design, type of intervention, and reported outcomes. Results: From the analysis of 10 studies, various interventions were found, including iron supplementation, combinations of iron and other micronutrients (folic acid, vitamin A, vitamin C), and food-based interventions. All interventions showed increased hemoglobin levels and improved anemia status, but adherence to treatment remains a challenge, especially in daily regimens. Conclusion: Appropriate supplementation interventions effectively reduce the prevalence of anemia in children. However, the management of side effects and the improvement of adherence are aspects that need further attention for long-term success.